The Chondro-Osseous Continuum: Is It Possible to Unlock the Potential Assigned Within? - Javaheri, Behzad; Caetano-Silva, Soraia P.; Kanakis, Ioannis; Bou-Gharios, George; Pitsillides, Andrew A. (Frontiers in Bioengineering and Biotechnology, 2018)
Endochondral ossification, by which long bones of the axial skeleton form, is a tightly regulated process involving chondrocyte maturation with successive stages of proliferation, maturation and hypertrophy, accompanied by cartilage matrix synthesis, calcification and angiogenesis, followed by osteoblast-mediated ossification. This developmental sequence re-appears during fracture repair and in osteoarthritic etiopathology. These similarities suggest that endochondral ossification, and the cells involved, are of great clinical importance for bone regeneration as it could provide novel targeted approaches to increase specific signalling to promote fracture healing, and if regulated appropriately in the treatment of osteoarthritis. The long-held accepted dogma states that hypertrophic chondrocytes are terminally differentiated and will eventually undergo apoptosis. In this mini review, we will explore recent evidence from experiments that revisit the idea that hypertrophic chondrocytes have pluripotent capacity and may instead transdifferentiate into a specific sub-population of osteoblast cells. There are multiple lines of evidence, including our own, showing that local, selective alterations in cartilage ECM remodelling also indelibly alter bone quality. This would be consistent with the hypothesis that osteoblast behaviour in long bones is regulated by a combination of their lineage origins and the epigenetic effects of chondrocyte-derived ECM which they encounter during their recruitment. Further exploration of these process could help to unlock potential novel targets for bone repair and regeneration and in the treatment of osteoarthritis.